การวิเคราะห์สถานการณ์การใช้แนวปฏิบัติทางคลินิกในหอผู้ป่วยอายุรกรรมชายโรงพยาบาลสันป่าตอง จังหวัดเชียงใหม่ - พราวเดือน เนตรวิชัย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Clinical practice guidelines (CPGs) for nurses are very important. CPGs are based on research and result in to the most effective practice for patients care. CPGs require the participation of all stakeholders in the health care team. The purpose of this study was to analyze the situation regarding the implementation of clinical practice guidelines in the Male Medical Ward at Sanpatong Hospital in Chiang Mai Province. The study involved a review of clinical practice guideline documents, and the participation of 1 Head Nurse, 4 nurses on the guidelines development team, and 8 nurse practitioners. Data were collected from documents, interviews, and focus groups. The instrumentation consisted of personal data record form, recording document form, as well as interview and focus group guides.The instruments were based on the concept of the Institute of National Health Medicine and Research Council Australia [1999, 2000] and validated by 3 expert nurses The personal data were analysed using descriptive statistics which included range, mean and standard deviation. The data from interviews and focus group were analyzed using content analysis. The results show the current status of clinical practice guideline implementation in the Male Medical Ward, Sanpatong Hospital, Chiang Mai Province. Study findings were as follows: 1) Printing and publishing: The clinical practice guidelines were made accessible through publication as booklets and summaries of guidelines were also available. Practitioners were prepared for guidelines use through meetings and training regarding the clinical practice guidelines. The problem encountered in this step, were that clinical practice guidelines were kept in a book and often could not be found when needed. The booklets were not attractive and the practitioners did not known them well, so no one was not familiar with their use. 2) The implementation guidelines: The development team was appointed to oversee guideline implementation which including supervision of guideline use and evaluation. A multidisciplinary team participated in sharing experiences to improve the quality of guideline implementation . Information technology was used to assist in the reporting metrics and incident reports. The problem in this step included a shortage of nursing staff and high workload. There were not enough leaders who were knowledgeable in clinical practice guidelines resulting in lack of continuity and no regular monitoring. 3) Evaluation: Continuity of the use of clinical practice guidelines was evaluated through examination of medical records every 3 months. Evaluation of performance outcomes was conducted by reviewing indicators and undesirable incidents. The problems identified was no continuous evaluation and evaluation results were not shared with practitioners. The findings of this study provide baseline information for management on the obstacles and suggestions for clinical practice guidelines in nursing practice. It is recommended that nurse administrators use this information to improve the quality of clinical practice guidelines implementation to improve quality of nursing care.